APPLICATION OF ZEOLITE IN AGRICULTURE - Astiana Sastiono (Jurnal Zeolit Indonesia, 2004)
Chemical and physical characteristic of zeolite are use not only as nutrient absorber to increases fertilizer efficiency, but also as compost mixing for plant growth media or compost humidity regulator. This agriculture advantages specially to increases nitrogen fertilizer efficiency. Many efforts carried out to minimize ammonia lost from nitrogen fertilizer, one of the alternatives is using zeolite through the process of making slow release fertilizer. As a mineral with the high rate of cation exchange capacity, zeolite have the ability to absorb ammonium ion, so it will increases nitrogen fertilizer efficiency by mixing zeolite with fertilizer or spreading zeolite into the fields. Zeolite urea capsules use on paddy plant on several regions on West Java showing production increasing and nitrogen fertilizer efficiency increases. Zeolite use as vegetables plant media showing a quite well result. Furthermore zeolite reduces heavy metal take over from the food chain. With these results zeolite have a big role in increasing agriculture production.